2017
DOI: 10.1111/jpc.13693
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medical students’ knowledge, attitude and practice towards human papillomavirus vaccination and their intention to recommend the vaccine

Abstract: Better HPV-related medical education may be a feasible way to promote the HPV vaccine in regions without universal coverage. Medical students who have not received the HPV vaccine should also be encouraged to receive the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
4
22
1
Order By: Relevance
“…In addition, research illustrates that knowledge is the most important predictor of HPV vaccine uptake (Mathur, Mathur, & Reichling, 2010), and that lack of HPV information is a major barrier of HPV vaccination intention (Zhuang, Wong, Chen, & Guo, 2016). Similarly, a previous study indicated that medical students with better HPV-related knowledge were more likely to receive HPV vaccination; furthermore, all domains of knowledge and attitude were positively associated with the intention to receive HPV vaccination among unvaccinated female students (Liu et al, 2018). A systematic review of studies examined that higher vaccine-related knowledge and positive attitudes toward the vaccine had a positive correlation with HPV vaccine uptake in teenage girls (Kessels et al, 2012).…”
Section: Hpv Prevention and Framed Messagessupporting
confidence: 57%
See 2 more Smart Citations
“…In addition, research illustrates that knowledge is the most important predictor of HPV vaccine uptake (Mathur, Mathur, & Reichling, 2010), and that lack of HPV information is a major barrier of HPV vaccination intention (Zhuang, Wong, Chen, & Guo, 2016). Similarly, a previous study indicated that medical students with better HPV-related knowledge were more likely to receive HPV vaccination; furthermore, all domains of knowledge and attitude were positively associated with the intention to receive HPV vaccination among unvaccinated female students (Liu et al, 2018). A systematic review of studies examined that higher vaccine-related knowledge and positive attitudes toward the vaccine had a positive correlation with HPV vaccine uptake in teenage girls (Kessels et al, 2012).…”
Section: Hpv Prevention and Framed Messagessupporting
confidence: 57%
“…In the current study, overall attitudes and intention regarding HPV vaccination baseline values were not too low; however, after watching the gain- or loss-HFMF, participants showed both significant increases in positive attitude and intention to receive the publicly funded HPV vaccine for cervical cancer prevention. Studies illustrated that negative attitudes, such as the fear of side effects and doubts regarding the efficacy of the HPV vaccine (Li et al, 2015; Trim, Nagji, Elit, & Roy, 2012), and vaccine safety concerns, such as hesitation toward HPV vaccination due to an underlying mistrust of the health care system or the belief that vaccinations cause disability, were main reasons against vaccine uptake (Liu et al, 2018). No matter whether school lecture courses (Kester et al, 2014) or hospital-based group education (Li et al, 2015) is provided, improving HPV-related knowledge could actually improve the attitude toward HPV vaccination, with the attitude toward HPV vaccination being more important than HPV-related knowledge (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Romania, the level of knowledge regarding HPV infection was significantly lower among students in the 1st year of medical school compared to 6thyear medical students, suggesting that some basic information is acquired during the program (33). In contrast, knowledge about HPV infections and the HPV vaccine among Slovenian medical students was relatively good, which is extremely important because it has previously been shown that increased awareness of HPV infections and vaccination among medical students is positively associated with higher vaccine uptake as well as their intention to recommend it (31). Moreover, the thought that future doctors favor HPV vaccination is especially encouraging because the fate of HPV vaccination will mostly be in their hands.…”
Section: Discussionmentioning
confidence: 95%
“…This group also bears the greatest burden of HPV infections because the prevalence of these infections is greatest in the late teens and early twenties (27). In contrast to Asian countries, where several studies evaluated knowledge, attitudes, and practices regarding HPV infections and vaccination among medical students (28)(29)(30)(31), these issues have not been thoroughly assessed among medical students in Europe. Two previous studies in Scotland and Romania (32,33) have shown significant gaps in medical student' knowledge.…”
Section: Discussionmentioning
confidence: 99%